APPLICATION OF EXPERT SYSTEM IN DIAGNOSING AUTOMATIC BARRIER GATE DAMAGE USING BAYES THEOREM - Taufik Nurul Ramadhan; Akhyar Lubis; Eko Haryanto (Sean Institute, 2022)
An expert system is a computer program tAn expert system can assist a layperson in resolving an issue by making a decision on a problem based on an expert's response. In general, a worker executes his job in an efficient manner that allows him to save money while working. As a result, most employees and entrepreneurs employ tools that assist humans in doing tasks that are simple and time-saving. There are various things that will require processes that are available at the barrier gate, given the performance power that can pick disconnected elements in the machine. The barrier gate system is a parking crossing facility for everyone who will enter and exit the parking lot at the shopping center through automatic crossing gates, where passengers can open the door first, and a parking data checking procedure using the barcode scanner available at the barrier gate is required. In expert systems, the Bayes theorem approach may be used to diagnose barrier gate damage and compute every conceivable symptom that exists in barrier gate damage. The proposed expert system may be utilized to diagnose existing barrier gate deterioration.